Information Security Theory and Practice. Smart Devices, Pervasive Systems, and Ubiquitous Networks Third IFIP WG 11.2 International Workshop, WISTP 2009, Brussels, Belgium, September 1-4, 2009, Proceedings - Markowitch, Olivier; Bilas, Angelos; Hoepman, Jaap-Henk.; Mitchell, Chris J.; Quisquater, Jean-Jacques.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This volume constitutes the refereed proceedings of the Third IFIP WG 11.2 International Workshop on Information Security Theory and Practice: Smart Devices, Pervasive Systems, and Ubiquitous Networks, WISTP 2009 held in Brussels, Belgium in September 2009. The 12 revised full papers presented were carefully reviewed and selected from 27 submissions for inclusion in the book; they are organized in topical sections on mobility, attacks and secure implementations, performance and security, and cryptography.
Mobility -- On the Unobservability of a Trust Relation in Mobile Ad Hoc Networks -- A Mechanism to Avoid Collusion Attacks Based on Code Passing in Mobile Agent Systems -- Privacy-Aware Location Database Service for Granular Queries -- Attacks and Secure Implementations -- Algebraic Attacks on RFID Protocols -- Anti-counterfeiting Using Memory Spots -- On Second-Order Fault Analysis Resistance for CRT-RSA Implementations -- Performance and Security -- Measurement Analysis When Benchmarking Java Card Platforms -- Performance Issues of Selective Disclosure and Blinded Issuing Protocols on Java Card -- Energy-Efficient Implementation of ECDH Key Exchange for Wireless Sensor Networks -- Cryptography -- Key Management Schemes for Peer-to-Peer Multimedia Streaming Overlay Networks -- Ultra-Lightweight Key Predistribution in Wireless Sensor Networks for Monitoring Linear Infrastructure -- PKIX Certificate Status in Hybrid MANETs.
Keywords: Computer science; Computer communication systems; Computer security; Data structures (Computer science).; Data encryption (Computer science).; Coding theory; Computer science -- Mathematics; Computer Science; Data Encryption; Computer Communication Networks; Systems and Data Security; Data Structures, Cryptology and Information Theory; Coding and Information Theory; Symbolic and Algebraic Manipulation; Electronic books